Emotions in Digital Learning: Assessing the Emotional and Pedagogical Impact of Historical Simulations through ChatGPT in University Classrooms - Rosser Limiñana, Pablo; Soler Ortiz, Seila (Octaedro, 2024)
This work investigates how historical simulations integrated with artificial intelligence affect university students’ emotional responses. With the increasing adoption of digital technologies in education, particularly post-COVID-19, this study utilizes a quasi-experimental design and the Positive and Negative Affect Schedule (PANAS) to measure specific emotions during simulations. The results reveal significant variations in students’ emotions, highlighting calm and empathy as predominant responses, although anxiety and distress are reported in different simulation phases. Implementing ChatGPT showed a significant impact on pedagogical interest and the perception of AI in education, suggesting that these technologies can be valuable tools to enrich students’ educational and emotional experiences. The study advocates for a thoughtful and ethical integration of AI in teaching, emphasizing the need for teacher training modules that prepare educators for an effective and conscious use of emerging technologies.
Es un capítulo del libro: Díaz-Noguera, M. D., Hervás-Gómez, C., Sánchez-Vera, F. (Coords.). (2024). Artificial Intelligence and Education (pp. 175-188). Octaedro.
Keywords: artificial Intelligence; historical simulations; emotions in learning; ChatGPT in education; student emotional responses